Osimertinib-related myotoxicity: a disproportionality analysis of the FDA adverse event reporting system - Yaqian Tan; Qi Song (BMC Cancer)
Abstract Background Osimertinib is a third-generation epidermal growth factor receptor tyrosine kinase inhibitor that has been widely applied as a standard first-line treatment in advanced non-small cell lung cancer. However, the risk signals of osimertinib-related myotoxicity have not yet been fully examined. This study aimed to explore osimertinib-related myotoxicity by conducting a real-world disproportionality analysis. Methods Data from January 1st 2015 to March 31st 2024 were retrieved from the U.S. Food and Drug Administration Adverse Event Reporting System database. Reporting odds ratio (ROR), proportional reporting ratio (PRR), and information component (IC) were employed to perform disproportionality analysis. Results A total of 121 cases with osimertinib-related myotoxicity were identified and analyzed. The adverse events were mostly reported in females (n = 74, 61.2%) and patients aged over 65 years old (n = 56, 46.3%). The median value of adverse event onset time was 40 (13.3, 164.5). Disproportionality analysis revealed that blood creatine phosphokinase increased (ROR025 = 5.00, IC025 = 2.07, PRR = 6.18), myositis (ROR025 = 2.72, IC025 = 1.26, PRR = 4.22), and myopathy (ROR025 = 1.28, IC025 = 0.63, PRR = 2.32) carried significant risk signals of osimertinib-related myotoxicity. Conclusions Our study comprehensively revealed the safety characteristics of osimertinib-associated myotoxicity. The results would offer referable evidence on the safety and prognosis of osimertinib.